Memory and power: (de-)statizing memories and (de-)centering State power - Blair, Elsa; Universidad de Antioquia (Editorial Pontificia Universidad Javeriana, 2011)
This paper intends to show, in first instance, the existence of some “artifacts” as devicesof memory, born out from various exercises conducted among communities havingundergone violence. These devices are the “living” embodiment of underground memoriesthat were gathered within various inquiry and extension projects by the researchgroup. In the second part, a more theoretical reflection is put forward on the Memory/Power relationship as the frame of discussion within which these experiences aresituated, emphasizing two aspects: making visible those “spaces of power” where bothmemories are situated within today’s Colombian society so as to show specifically howthose spaces of power appear, as well as the instruments they make use of, qualifyingmemories either as dominant or underground; and to show those spaces, just like anyother social process, are not immutable or unchangeable phenomena, but are proneto be transformed, redefined and even reconfigured up to leading all the way to makechanges to differently distribute the resources of power leaving their mark on them.In a third final part, a reflection “as a working hypothesis” is made, which could bethe way to change the issue at hand and suggest new paths aiming to shift the placein society for those underground (marginal, hidden and scarcely visibilized) memoriesand make them emerge to surface so that they can develop all of their political potentialand get their due place in Colombia’s historical memory.